2017
DOI: 10.1163/22134468-00002081
|View full text |Cite
|
Sign up to set email alerts
|

Time Perspective in Late Adulthood: Aging Patterns in Past, Present and Future Dimensions, Deviations from Balance, and Associations with Subjective Well-Being

Abstract: We examined cross-sectional aging patterns for subscales of the Swedish version of the Zimbardo Time Perspective Inventory in a population-based sample of older adults (60–90 years; N = 447). Alternative methods to assess time perspective balance (DBTP, involving a single Future dimension; S-BTP; and DBTP-E, including in addition, Future Negative), were compared and their relations to subjective well-being (SWB) were examined. Significant negative age relations were observed for Past Negative and Future Negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 4 publications
5
54
0
Order By: Relevance
“…where o = observed and e = expected score; ePN = 1.95, ePP = 4.60, ePF = 1.50, ePH = 3.90, eF = 4.00, eFN = 1.8 (Rönnlund et al 2017). The outcome measure is the deviation from balanced time perspective (DBTP), where the lower the DBTP score the more balanced the TP profile.…”
Section: Methodsmentioning
confidence: 99%
“…where o = observed and e = expected score; ePN = 1.95, ePP = 4.60, ePF = 1.50, ePH = 3.90, eF = 4.00, eFN = 1.8 (Rönnlund et al 2017). The outcome measure is the deviation from balanced time perspective (DBTP), where the lower the DBTP score the more balanced the TP profile.…”
Section: Methodsmentioning
confidence: 99%
“…Research has for instance shown that individual differences in time perspective can predict reactions to traumatic events [9], and that time perspective, and particularly Past Negative, is associated with depression and neuroticism [10]. Recent time perspective research has also underlined the importance of Future Negative, which has been associated with maladaptive coping strategies in late adolescence [11] and negatively associated with well-being among older adults [12]. …”
Section: Anxiety Time Perspective and Repetitive Negative Thinkingmentioning
confidence: 99%
“…Once crystallized, such temporal Bbiases^might be regarded as stable dispositions that increase vulnerability to mental ill health and maladaptive behaviors Boyd 1999, 2008). A corollary to this position is that there is an optimal, or balanced, time perspective (BTP) that promotes subjective wellbeing and mental health Boyd 1999, 2008), an idea that sparked much recent interest (e.g., Mooney et al 2017;Rönnlund et al 2017; for a review, see Stolarski et al 2015).…”
mentioning
confidence: 99%
“…In an extended version of the ZTPI, the Swedish ZTPI (S-ZTPI; Carelli et al 2011), this aspect is taken into account by a separate Future Negative scale. Based on this rationale, Rönnlund et al (2017) suggested an alternative version of DBTP that also incorporates Future Negative. A direct comparison between DBTP with and without the inclusion of Future Negative indeed showed that inclusion of Future Negative within the DBTP operationalization was more strongly associated with well-being (Rönnlund et al 2017) and with perceived stress (Rönnlund et al 2018).…”
mentioning
confidence: 99%